PENGEMBANGAN DESAIN KEMASAN PRODUK KOPI DJAMUDJU ROAST BEAN BERDASARKAN PREFERENSI KONSUMEN MENGGUNAKAN METODE KANSEI ENGINEERING - Munandar, Ahmad; Fahrulrozi, Muhamad (TECHNO-SOCIO EKONOMIKA, 2024)
The domestic coffee industry is quite diverse, ranging from small-scale industries to the international coffee market. One of the MSMEs producing processed coffee in the city of Bandung is Djamudju Roast Bean. The problem that occurs in the coffee business is the decline in sales and some shortcomings in consumer assessments regarding the quality and appearance of coffee packaging. The product development strategy that can be done is by developing primary packaging. Therefore, it is necessary to develop product packaging design according to consumer preferences. The objective achieved is to produce coffee packaging design according to consumer preferences using the Kansei Engineering method. Application of Kansei Engineering Method, using 20 Kansei Words with 5 packaging design elements (material, label, shape, color, and accessories). Questionnaires were given to 67 respondents to find out consumer preferences for Djamudju Roast Bean coffee packaging and 16 samples of similar coffee packaging. Conjoin analysis was conducted to determine the relationship between 20 Kansei words and 5 coffee packaging design elements (material, label, shape, color, and accessories). Based on the results obtained, the design of a combination of coffee packaging in accordance with consumer preferences based on 20 Kansei words is packaging with aluminum foil material, with digital printing labels, gusset pouch shapes, many colors and zipper lock accessories. It is expected that from the new packaging design based on consumer preferences, the product will be able to compete in the market in a sustainable manner.